Function analysis of differentially expressed microRNAs in TGF-β1-induced cardiac fibroblasts differentiation. Issue 10 (11th October 2019) - Liu, Suxuan; Ke, Wen; Liu, Yang; Zhao, Zhenzhen; An, Lina; You, Xiaohua; Yang, Fan; Yang, Xiangqun; Wang, Guokun; Zhao, Xianxian
Abstract: Background: Cardiac fibroblasts differentiation plays a critical role in cardiac remodeling and failure, but the underlying molecular mechanisms are still poorly understood. MicroRNAs (miRNAs) had been identified as important regulators during cell differentiation. The aim of the present study was to screen the miRNAs involved in regulation of cardiac fibroblasts differentiation. Methods: The differentiation of rat cardiac fibroblasts into myofibroblasts was induced by transforming growth factor-β1 (TGF-β1). Small RNA sequencing was then applied to detect the differentially expressed miRNAs. Results: A total of 450 known miRNAs were detected, and 127 putative novel miRNAs were predicted by miRDeep2 analysis. DEGseq analysis and qRT-PCR confirmed that 24 known miRNAs were differentially expressed in TGF-β1-induced cardiac fibroblasts, including three up-regulated miRNAs and 21 down-regulated miRNAs. After miRNAs target genes prediction by miRanda algorithm, pathway analysis showed that these potential target genes were involved in Calcium signaling pathway, Type II diabetes mellitus, and Glutamatergic synapse pathway, etc. Meanwhile, seven putative miRNAs were also detected differentially expressed during TGF-β1-induced cardiac fibroblasts differentiation. Conclusions: These differentially expressed miRNAs might play critical roles in cardiac fibroblasts differentiation. Altered expression of miRNAs may yield new insights into the underlying mechanisms of cardiac fibrosis and provide novel mechanism-based therapeutic strategies for cardiac fibrosis.